Extraction and surface modification of cellulose fibers and its reinforcement in starch-based film for packaging composites - Halimatun Saadiah Hafid; Farah Nadia Omar; Ezyana Kamal Bahrin; Minato Wakisaka (Springer Nature, 2023)
Background Cellulose extraction from gloss art paper (GAP) waste is a recycling strategy for the abundance of gloss art paper waste. Here, a study was conducted on the impact of ultrasonic homogenization for cellulose extraction from GAP waste to improve the particle size, crystallinity, and thermal stability. Results At treatment temperature of 75.8 °C, ultrasonic power level of 70.3% and 1.4 h duration, cellulose with properties of 516.4 nm particle size, 71.5% crystallinity, and thermal stability of 355.2 °C were extracted. Surface modification of cellulose GAP waste with H3PO4 hydrolysis and 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO) oxidation was done followed by starch reinforcement. Surface hydrophobicity and mechanical strength were increased for H3PO4 hydrolysis and TEMPO oxidation starch–cellulose. No reduction of thermal properties observed during the treatment, while increment of crystallinity index up to 47.65–59.6% was shown. Neat starch film was more transparent, followed by starch–TEMPO film and starch–H3PO4 film, due to better homogeneity. Conclusions The cellulose GAP reinforced starch film shows potential in developing packaging materials and simultaneously provide an alternative solution of GAP waste recycling.